A darkness more than night - Connelly, Michael, 1956- (Connelly, Michael, 1956- Harry Bosch series., 2014)
Terry McCaleb, the retired FBI agent who starred in the bestseller "Blood Work," is asked by the LAPD to help them investigate a series of murders that have them baffled. They are the kind of ritualized killings McCaleb specialized in solving with the FBI, and he is reluctantly drawn from his peaceful new life back into the horror and excitement of tracking down a terrifying homicidal maniac. More horrifying still, the suspect who seems to fit the profile that McCaleb develops is someone he has known and worked with in the past: LAPD homicide detective Harry Bosch.